Do corporate directors 'heap' dividends? Evidence on dividend rounding and information uncertainty in Australian firms. Issue 3 (August 2018) - Nam, Yoonsoo; Niblock, Scott J; Sinnewe, Elisabeth; Jakob, Keith
In this study, we examine the extent of dividend heaping in Australian firms between 1976 and 2015. Our findings show that 27.39% of dividends greater than or equal to 2.5-cents are heaped in 2.5-cent intervals, while 70.90% of dividends less than 2.5-cents are heaped in 0.25-cent intervals. We find that the heaping phenomenon decreases over time and average dividend size increases. We also show that when establishing the likelihood of dividend heaping, stock return volatility and firm size are consistent with the information uncertainty hypothesis. Dividend heaping also appears to be influenced by firm-level characteristics that are inconsistent with the hypothesis. For instance, the likelihood of heaping increases with dividend size and firm age.